Pengaruh Brand Association, Brand Awareness, dan Perceived Quality terhadap Keputusan menggunakan Jasa Gojek: (Studi Kasus Mahasiswa S1 Manajemen Universitas Mataram) - Hartoni, Wanda Sriningsi; Hamdi, Nizar; Siswanto, Topan; Zulkarnaen (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This study aims to test the partial, simultaneous and dominant influence of Brand Association, Brand Awareness, and Perceived Quality on the decision to use Gojek services. The population of this study were undergraduate students of Management at Mataram University. The sample was taken using purposive sampling, with the criteria of undergraduate students of management at Mataram University who had used Gojek transportation more than 2 times. Data were analyzed using multiple linear regression, T test, F test, beta coefficient test. The results of the T test study obtained that Brand Association had a significant partial effect on the decision to use Gojek services. This can be seen from the significance value of 0.046 <0.05. Perceived Quality had a significant partial effect on the decision to use Gojek services. This can be seen from the significance value of 0.000 <0.05. then Brand Awareness did not have a significant partial effect on the decision to use Gojek services. This can be seen from the significance value of 0.613> 0.05. From the F test, the results obtained were that Brand Association, Brand Awareness, and Perceived Quality had a significant simultaneous effect on the decision to use Gojek services. seen from the significance value of 0.000 < 0.005 and the calculated f value and f table of 23.643 > 2.92. From the beta coefficient test, the most dominant value was obtained, namely Perceived Quality of 0.460.